2009
DOI: 10.1186/1746-1596-4-48
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor-like lesion of the urinary bladder: a report of two cases and literature review; giant cell tumor or undifferentiated carcinoma?

Abstract: SummaryGiant cell tumor, excluding its prototype in bone, is usually a benign but local aggressive neoplasm originating from tendon sheath or soft tissue. Malignant behavior is uncommon. Visceral organ involvement including urinary bladder is rare. Giant cell tumors in visceral organs usually accompany epithelial tumors and the clinical behavior of giant cell tumor in urinary bladder is similar to its bone counterpart. Here, we report two cases of giant cell tumor located in urinary bladder in comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…ORUCUT has been rarely described in the literature with approximately 20 case reports and small case series reported to date [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The largest prior case series by one of the current authors (JIE) on only six cases concluded that the mononuclear cells in ORUCUT were derived from urothelium based on three main findings: (1) the presence of at least focal epithelial staining (either AE1/3, Cam5.2, CK7 and or EMA) in 4/6 cases;…”
Section: Discussionmentioning
confidence: 99%
“…ORUCUT has been rarely described in the literature with approximately 20 case reports and small case series reported to date [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The largest prior case series by one of the current authors (JIE) on only six cases concluded that the mononuclear cells in ORUCUT were derived from urothelium based on three main findings: (1) the presence of at least focal epithelial staining (either AE1/3, Cam5.2, CK7 and or EMA) in 4/6 cases;…”
Section: Discussionmentioning
confidence: 99%
“…Mixed histology is also seen in other rare primary bladder tumors such as adult rhabdomyosarcoma [15] or giant cell tumor [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies of the ectopic overexpression of vimentin have shown the invasive behavior of epithelial carcinoma cells, which reveal the association of vimentin with tumor invasiveness and motility 84, 85. One previous study found expression of VIM in mononuclear cells of GCTB 86. Our results show that the increased expression of vimentin in multinucleated giant cells, stromal cells and monocytic cells of GCTB is significantly associated with GCTB, and therefore, the increased expression of vimentin may act as a new indicator of this tumor.…”
Section: Discussionmentioning
confidence: 99%